Evaluación de lesiones histopatológicas del aparato reproductor de los carneros infectados experimentalmente con Brucella ovis - Sánchez Orozco, Adrián (Universidad Michoacana de San Nicolás de Hidalgo, 2022)
Infectious epididymitis of rams is a disease caused by bacteria of the genus Brucella ovis (B. ovis), it is characterized by infertility, investigations have been developed to know more about its diagnosis, so it is important to know more about lesions caused by B. ovis in the reproductive system of rams. This investigation was done in the Histopahology area of the Unit of Auxiliary Services for Diagnosis (UASD) in the Faculty of Veterinary Medicine and Zootechnics at the Universidad Michoacán de San Nicolas de Hidalgo, it is located on highway 9,5 Morelia-Zinapécuaro, Michoacán. México. Histopathological studies were evaluated from three groups of rams: Group n=1 Inoculation route mucosal, instillation of B. ovis inoculum (01 Zac-INIFAP) in conjunctival (left) and preputial mucosa of 0,5 mL with concentration of 3,9X109 Colony Forming Units (CFU) in both mucosal membranes. Group n=2 Inoculation of B. ovis (01 Zac-INIFAP) intravenous route of 1 mL of inoculum un jugular vein at the same concentration 3,9X109 CFU. Control group n=3, received conjunctival (left) and preputial installation of phosphate saline solution (SS), of 0,5 mL in the conjunctival and foreskin routes.

La Epididimitis infecciosa de los carneros es una enfermedad producida por bacterias del género Brucella ovis (B. ovis), es caracterizada por causar infertilidad, se han desarrollado estudios para conocer más respecto a su diagnóstico, por lo que es importante conocer más de las lesiones que produce en el aparato reproductor de los carneros. El trabajo se desarrolló en el área de Histopatología de la Unidad de Servicios Auxiliares para el Diagnóstico (USAD) dela Facultad de Medicina Veterinaria y Zootecnia de la Universidad Michoacana de San Nicolás de Hidalgo, ubicada en la carretera 9,5 de la carretera Morelia–Zinapécuaro, Michoacán, México. Los cortes histopatológicos se evaluaron a partir de tres grupos de carneros: Grupo n=1 Inoculación en mucosa, instilación de inoculo de B. ovis (01Zac-INIFAP) en mucosa conjuntival (izquierda) y prepucial con 0.5 mL a una concentración de 3,9X109 Unidades Formadora de Colonias (UFC) en ambas mucosas. Grupo n=2 inoculación de B. ovis (01Zac-INIFAP) vía intravenosa administrando 1 mL de inóculo en vena yugular a la misma concentración 3,9X109 UFC. Grupo n=3 control al que se le administró instilación conjuntival (izquierda) y prepucial de solución salina de fosfato (SSF), a razón de 0,5 mL tanto en conjuntiva como en prepucio.
Facultad de Medicina Veterinaria y Zootecnia. Maestría en Desarrollo Tecnológico en Sistemas de Producción Animal
Keywords: info:eu-repo/classification/cti/6; FMVZ-M-2022-0797; Reproductor; Carneros; Histopatología; http://bibliotecavirtual.dgb.umich.mx:8083/xmlui/handle/DGB_UMICH/8409